Contract (re-)negotiation with private and common values - Vitali Gretschko; Achim Wambach (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We analyze the contracting problem of a principal who faces an agent with private information and cannot commit to not renegotiating a chosen contract. We model this by allowing the principal to propose new contracts any number of times after observing the contract choice of the agent. We propose a characterization of renegotiation-proof states of this (re-)negotiation and show that those states are supported by a perfect Bayesian equilibrium of an infinite horizon game. The characterization of renegotiation-proof states provides a tool, which is both powerful and simple to use, for finding such states in specific environments. We proceed by applying the results to adverse selection environments with private and common values. We show that with private values and common values of the "Spence" type only, fully efficient and separating states can be renegotiation-proof. With common values of the "Rothschild-Stiglitz" type inefficient and (partial) pooling states may be renegotiation-proof.
urn:nbn:de:bsz:180-madoc-437510
Keywords: C73; C78; D82; 330; principal-agent models; renegotiation; Coase-conjecture